Serum acid phosphatase level - is it a marker for diagnosis of malaria - Devi, C. Suvarna; Nadiger, H. A.; Krishna, T. Sharmila; Naidu, J. N. (International Journal of Research in Medical Sciences, 2017)
Background: Malaria is endemic throughout most of the tropics. Technically, detection of malaria parasite may be missed due to low parasite density at sampling time and poor blood film preparation. The study was aimed to evaluate the serum acid phosphatase levels as a possible diagnostic marker for malarial infections. Methods: This study was conducted on a total of 100 subjects (40 malaria cases, 30 non-malarial cases and 30 sex and age matched healthy controls attending the department of medicine, PESIMSR, Kuppam. Venous blood sample was collected and serum acid phosphatase (ACP) level estimation was be done by enzymatic method using commercial kit (Raichem diagnostics kit). Results: Serum ACP level was highly significantly elevated in malarial group (Mean±SD) (3.14±1.22) when compared with control (1.33±0.72) and non-malarial (1.81±0.30) groups (P value <0.001.). Conclusions: In this study, there was a significant increase in the serum ACP levels in malarial patients as compared to other groups. This suggests that serum ACP levels can be used as a marker for malaria.